1991
DOI: 10.1007/bf00403186
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of islet amyloid polypeptide and its carboxy terminal flanking peptide in islets of diabetic man and monkey

Abstract: Islet amyloid polypeptide is a normal constituent of islet Beta cells and is derived from a larger precursor by removal of flanking peptides at the carboxy (C) and amino (N) terminals. The role of these flanking peptides in the formation of amyloid in Type 2 (non-insulin-dependent) diabetes mellitus and in insulinomas is unknown. The C-terminal flanking peptide of islet amyloid polypeptide was localised by immunocytochemistry in human and monkey pancreatic islets from Type 2 diabetic and non-diabetic individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…IAPP is colocalised with insulin in the secretory granules of islet fl-cells and co-secreted in response to fl-cell secretagogues [3,4]. IAPP has been identified in all species examined so far [5] and, in common with other secretory peptides, is synthesized as a larger precursor molecule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IAPP is colocalised with insulin in the secretory granules of islet fl-cells and co-secreted in response to fl-cell secretagogues [3,4]. IAPP has been identified in all species examined so far [5] and, in common with other secretory peptides, is synthesized as a larger precursor molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Islet amyloid polypeptide (IAPP), 'amylin', is a component peptide of amyloid fibrils deposited in islets of type 2 diabetic patients [1,2]. IAPP is colocalised with insulin in the secretory granules of islet fl-cells and co-secreted in response to fl-cell secretagogues [3,4]. IAPP has been identified in all species examined so far [5] and, in common with other secretory peptides, is synthesized as a larger precursor molecule.…”
Section: Introductionmentioning
confidence: 99%
“…However, we have earlier shown in an immunohistochemical study that the N-terminal fragment of IAPP can occur in islet amyloid [29]. Others have failed to find the Cterminal flanking peptide in islet amyloid [2]. Interestingly, however, it has also been shown that proIAPP can form amyloid like fibrils in vitro [7].…”
Section: Introductionmentioning
confidence: 99%